Malignant transformation rate based stratification model for oral potentially malignant disorders: A potential idea - Gargi S. Sarode; Sachin C. Sarode; Nikunj Maniyar; Roney Sam Regi; Aakriti Aruna; Shankargouda Patil (Elsevier, 2020)
By the virtue of heterogeneous biological aggressiveness, oral potentially malignant disorders (OPMDs) comprise the ideal group of disorders for biological behavior-based classification system. Concerning the exponentially increasing incidence and mortality of oral squamous cell carcinoma (OSCC), it has now become a need of the hour to formulate a classification system for OPMDs that even a general dental surgeon could apply in everyday clinical practice. With this view in mind, efforts have been made to stratify various OPMDs based on their malignant transformation rate (MTR). Databases like PubMed, SCOPUS, Web of Science and CINHAL were used for searching the appropriate papers. Preferences were given to meta-analyses and cohort studies for determining the value of MTRs. In other cases, cross-sectional studies, case series and case reports were consulted for obtaining the values. Based on the MTRs obtained, we stratified all the OPMDs into 3 groups: Low risk group (MTR: 0-3%), Moderate risk group (MTR: 4-15%) and High risk group (MTR: above 15%), based on their MTRs available from the literature so far. The idea proposed in the paper can aid researchers and clinicians in identifying and planning treatment strategies that can be generalized to different OPMDs included in the same group. Since the paper is not based on a cohort study or a meta-analysis, the authors recommend a systematic review and meta-analysis to be carried out for a clinically applicable classification based on the proposed idea.